Manajemen Sumber Daya Manusia Berbasis Kearifan Lokal; Study Etnografi Tradisi Cembengan Di Pabrik Gula Madukismo, Yogyakarta - Zuhri, Saifudin; Harsono, Mugi; Wening, Nur (Kajian Ekonomi dan Bisnis, 2018)
This study aims to understand the meaning of the Cembengan tradition as the local wisdom of the Yogyakarta community in maintaining human resource management at the Madukismo sugar factory in Yogyakarta. This study uses a qualitative approach to ethnographic study with data collection techniques through indepth interviews, participatory observation, documentation, and triangulation. This study produces findings that traditions based on local wisdom have a positive contribution to the maintenance of human resources in the Madukismo sugar factory. By the workers and the community around the sugar factory Cembengan is interpreted not only as a mystical ritual but has a meaningful function (meaning) in articulating the ritual values into the concepts of safety, tranquility, motivation, teamwork, cohesiveness and harmony with the community around the factory and natural environment. The results of this study also explain that the meaning contained in local traditions can be operationally transformed in HR management practices, especially for the maintenance of human resources involved in corporate policy making and the production process so that common goals can be achieved.